Metabolic modeling software for metabolic assessment of diabetic patients - Lee, Chew Tin; Abdul Majid, Fadzilah Adibah; Cheng, Kian Kai (Faculty of Chemical and Natural Resource Engineering, 2008)
An individualized assessment of metabolic health through modeling has been viewed as the future trend in health care to improve and guide the overall metabolism towards an optimal personal metabolic state. This method could be a potential tool for the prevention of metabolic diseases such as type 2 diabetes. In this study, a software was developed to model the major metabolic pathways related to type 2 diabetes. The metabolic model in this study consists of three experimentally validated models found in the literatures. The three models include a whole-body glucose regulation system known as the Cobelli model, an insulin signaling pathways and an insulin secretion model. The three models were first simulated separately to ensure reproducibility of the results in the literatures. They were later combined, simulated and compared with the literatures. The combined model enables the study of metabolic behavior with continuous input, as opposed to transient step input originally used in most studies. A graphic-user-interface (GUI) was also built to the combined model. Based on the results of the study, it was found that the software is capable of predicting the behaviors of cellular metabolites under the induction of different external input. It could serve as a potential platform for the assessment of type 2 diabetes, helps in experimental and clinical trial design, and a potential application in drug discovery. These may help in the prevention and treatment of type 2 diabetes.